Pengaruh Implementasi E-Government dan Partisipasi Masyarakat Terhadap Kinerja Pemerintah Desa dengan Good Government Governance sebagai Variabel Pemoderasi - Rizal Yaya; Sukardi Sukardi (Universitas Muhammadiyah Palembang, 2025)
This study aims to examine the effect of e-government implementation and community participation on village government performance with Good Government Governance (GGG) as a moderating variable. The study was conducted in Bantul Regency, Special Region of Yogyakarta, with respondents consisting of members of the Village Consultative Body, Village Council, and Village Community Empowerment Institution. Data were collected through questionnaires and analyzed using the SEM-PLS method with the help of SmartPLS v.4.0 software. The results of the study indicate that e-government implementation and community participation have a significant positive effect on village government performance. GGG is proven to strengthen the effect of e-government implementation on village government performance, but is not significant in moderating the effect of community participation on village government performance. These findings provide important implications for village governments in improving performance through the implementation of e-government and community participation, by considering the principles of GGG